IDENTIFICATION OF CAUSING FACTORS FOR THE NON-APPLICATION OF SMK3 BASED ON ISO 45001 CLAUSES 6,7,8 AT PT X IN 2024 - RIZKI HERWANSYAH; LYDIA DARMIYANTI; INDRIASARI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2024)
Occupational Safety and Health Management is the process of controlling risk and creating a safe and productive work environment which is a component of the company's management system. Factors that hinder companies from implementing SMK3 in accordance with ISO 45001 are the lack of support from management to implement SMK3 and safety officers who are not competent in their fields. This study is a descriptive qualitative study where data collection is carried out directly on workers, in-depth interviews and filling out questionnaires, with a research sample of 18 respondents. The results of the study showed that the company had not implemented SMK3 based on ISO 45001, from the results of observations, interviews and filling out questionnaires. Respondents on average did not know more about SMK3, because safety officers did not socialize the K3 policy regarding SMK3 in accordance with ISO 45001. The company must conduct general K3 expert training and other training related to K3 for safety officers so that officers are competent, and provide more support from management and others so that SMK3 can be implemented in the company